Stress-corrosion cracking of pipe steel under complex influence of factors. (October 2020) - Nyrkova, Lyudmila
Abstract: The stress-corrosion cracking (SCC) of X70 type steel of a controllable rolling for manufacture of pipes was studied in the conditions of complex influence of factors such as full immersion into the solution and periodic wetting, open circuit potential and cathodic polarization potentials (−0.75 Vs.c.e., −1.0 V, −2.0 V), accumulated cyclic stresses simulating a long operation of the gas pipeline, presence of stress concentrator in the form of a notch, influence of protective polymeric coatings with different transition resistance and their combinations. Different combinations of stress-corrosion factors were simulated in the laboratory, their influence on the X70 type steel of a controllable rolling for manufacture of pipes was investigated and the susceptibility of that steel to SCC under these conditions was estimated. The KS coefficient (the ratio of the relative reduction of the sample in air to its relative reduction in the solution) was proposed for estimating the sensibility to SCC. The results of investigations confirmed that mechanical stresses, corrosion-aggressive medium and protective potential are the main factors, while other ones are additional and can increase or decrease the influence of the main factors, without changing the process mechanism.